2019
DOI: 10.1159/000499341
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic-Renal Disease in South Asians: Consensus Recommendations from the Cardio Renal Society of America

Abstract: Background: Rates of cardiometabolic-renal disease are extremely high among South Asians (India, Pakistan, Bangladesh, Sri Lanka, Bhutan, the Maldives, and Nepal) residing in their home countries and worldwide. The Cardio Renal Society of America, National Kidney Foundation of Arizona, and Twinepidemic Inc. convened a task force to examine evidence and reach consensus regarding cardiometabolic-renal disease prevention in South Asians. The task force distilled the findings from 5 years of face-to-face and virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…16 In Southeast Asia, excess salt intake is part of culinary culture, which results in increased consumption of daily salt in this region. 17 However, the habit of adding salt during dinning is dangerous. Our study showed an association of discretionary salt use with male gender which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…16 In Southeast Asia, excess salt intake is part of culinary culture, which results in increased consumption of daily salt in this region. 17 However, the habit of adding salt during dinning is dangerous. Our study showed an association of discretionary salt use with male gender which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these nine risk factors, such as smoking, history of hypertension or diabetes, waist-hip-ratio, dietary patterns, physical activity, consumption of alcohol, blood apolipoproteins, and psychosocial factors; all of them accounted for 90% of the PAR in men and 94% in women. South Asians have been found to have a higher proportional incidence and mortality rate from ischemic heart disease and CKD compared with other ethnic groups such as East Asian (Chinese, Japanese, and Korean) populations and non-Hispanic whites[ 6 ].…”
Section: Introductionmentioning
confidence: 99%